Analysis of Determinants of Profit of Cukli Rungkang Jangkuk Craftsmen, Sayang- Sayang Village, Mataram City - Johan, Rohmiatun Rapiah; Ahmad Amir Aziz; Mariaton Sadiah (Universitas Hamzanwadi, 2024)
This research aims to determine the influence of working capital, labor, business experience and product diversity on the profits of Cukli Rungkang Jangkuk artisans, Sayang- Sayang Village, Mataram City. The method used in this research is Multiple Linear Regression Analysis. This research sampled all Cukli Rungkang Jangkuk Craftsmen, namely 115 people. Based on the research results, it can be concluded that Working Capital (X1) has a positive and significant effect on the profits of Cukli Rungkang Jangkuk artisans located in Sayang- Sayang Subdistrict, Mataram City, because the value of tcount > ttable is 7.919 > 1.982 with a significance value of 0.000 < 0, 05. Meanwhile, labor, business experience and product diversity do not significantly affect the profits of Cuki Rungkang Jangkuk artisans in Sayang-sayang sub-district, Mataram City. Meanwhile, the results of simultaneous testing of working capital, labor, business experience and product diversity have a significant effect on the profits of Cukli Rungkang Jangkuk artisans in Sayang- Sayang sub-district, Mataram City.